Qualities of exemplary nurse leaders: perspectives of frontline nurses. (4th July 2013) - Anonson, June; Walker, Mary Ellen; Arries, Ebin; Maposa, Sithokozile; Telford, Patti; Berry, Lois
<x xml:space="preserve">Abstract</x> Aim This paper reports on a study that looked at the characteristics of exemplary nurse leaders in times of change from the perspective of frontline nurses. Background Large‐scale changes in the health care system and their associated challenges have highlighted the need for strong leadership at the front line. Methods In‐depth personal interviews with open‐ended questions were the primary means of data collection. The study identified and explored six frontline nurses' perceptions of the qualities of nursing leaders through qualitative content analysis. This study was validated by results from the current literature. Results The frontline nurses described several common characteristics of exemplary nurse leaders, including: a passion for nursing; a sense of optimism; the ability to form personal connections with their staff; excellent role modelling and mentorship; and the ability to manage crisis while guided by a set of moral principles. All of these characteristics pervade the current literature regarding frontline nurses' perspectives on nurse leaders. Conclusion This study identified characteristics of nurse leaders that allowed them to effectively assist and support frontline nurses in the clinical setting. Implications for nursing management The findings are of significance to leaders in the health care system and in the nursing profession who are in a position to foster development of leaders to mentor and encourage frontline nurses.